The Strategy of Corporate Social Responsibilty: Assimilation of Nature and Local Culture - Kardiyati, Endah Nurhawaeny; Wijaya, Mahendra; Suwarto; Supriyadi (International Journal of Psychosocial Rehabilitation, 2020)
Abstract- From the midst of the 20th century, CSR has grown significantly as a field of academic attention. Many authors agree that companies undertake activities of a limited nature, which do not always meet the expectations of local communities. This study is about how CSR can play a role in assimilating nature with local culture. This inquire about was within PT Indocement Tunggal Prakarsa Tbk, Indonesia. This investigation is included within the sort of subjective investigate and the inquire about procedure used in this ponder be a case study about. The essential information was science and innovation assimilation through CSR programs by in-depth interviews, perceptions and documentation. The collected information are analyzed by triangulation and source survey. This research formulates findings about the scope and exercises of community strengthening within the utilization of natural waste for batik coloring.